PEMANFATAN MEDIA SOSIAL UNTUK DIGITAL MARKETING KERAJINAN VINIL DI DUSUN CODE, TRIRENGGO KABUPATEN BANTUL, DIY - Sumarmi, Saptaningsih; Wicaksono, Suryo Wisnu; Prakoso, Dindo Wahyu; Lutfionesti, Dwi Alrasta; Saputra, Koko Endra; Putra, Candra Dwi (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Vinyl crafts Jogja in Code hamlet, Trirenggo, Bantul district, still produces products according to orders and markets products traditionally. This service activity aims to provide knowledge to digital marketing, online media creation, and implementation assistance. The method of implementing community service activities is carried out offline and online, by combining theory and practice, and showing assistance in program implementation until it is successful. A program that offers training and mentoring related to digital marketing, logo creation is the solution offered to solve problems that have been identified. The result of this activity is that producers are able to create online media for digital marketing, have company logos, create marketplace stalls on Instagram and Facebook. The conclusion of this activity is digital marketing can be a solution to increase the marketing reach of Vinyl Jogja crafts. Abstrak. Kerajinan Vinyl Jogja di dusun Code, Trirenggo, kabupaten Bantul, masih memproduksi produk sesuai pesanan, dan memasarkan produk secara tradisional. Kegiatan pengabdian ini bertujuan untuk memberikan pengenalan tentang digital marketing, pembuatan media online, dan pendampingan implementasinya. Metode pelaksanaan kegiatan pengabdian dilakukan secara daring dan luring, dengan mengkombinasikan teori dan praktik, serta dilanjutkan dengan pendampingan implementasi program sampai berhasil. Program pemberian pelatihan dan pendampingan terkait digital marketing, pembuatan logo menjadi solusi yang ditawarkan untuk mengatasi permasalahan yang sudah diidentifikasi. Hasil dari kegiatan ini adalah produsen mampu membuat media online untuk digital marketing, memiliki logo perusahaan, membuat lapak marketplace di Instagram dan facebook. Kesimpulan kegiatan ini adalah digital marketing dapat menjadi solusi untuk peningkatan jangkauan pemasaran kerajinan Vinyl Jogja.